Thermal biology of aphids and implications for agriculture and food security - Villena, O.C.; Arab, A.; Armbruster, P.A.; Markovich, E.; Zhang, K.; Tonnang, H.E.; Sokame, B.M.; Kreuze, Jan F.; Carhuapoma, Pablo; Gamarra, H.; Johnson, L.R. (2024)
Climate change poses significant challenges to agriculture and food security, particularly through its effects on insect vector populations and the pathogens they transmit. Aphids are one of the biggest group of ectotherms that transmit viruses to plants; more than 200 species have been identified as pathogen vectors. These aphids are responsible for transmitting over 300 viruses. The life-history traits of aphids such as fecundity and survival respond strongly and non-linearly to temperature and therefore to global warming. In this study, we elaborate the thermal responses for the main life-history traits (i.e, development and mortality rate) for aphid species for which data were available or generated. Also, thermal responses for virus transmission rates were elaborated to describe plant host to vector and vector to plant host dynamics. With these data, we elaborated thermal suitability models which were used to map current and projected scenarios for the transmission of viruses by aphids. Data was only available/generated for 19 aphid species, many of which only have data either at the lower or upper thermal limits. For virus transmission rates, from host plant to vector and from vector to plant data was only available/generated for potato virus Y (PVY), potato virus A (PVA), and potato leaf roll virus (PLRV) transmitted by the aphid Myzus persicae. Projections show that virus transmission by aphids will shift to northern latitudes. Understanding the thermal biology of aphids is crucial for developing effective measures to safeguard agriculture, especially staple crops, and food security in the context of climate change.